A novel molecular and chromosomal lineage of the anthropophilic Simulium (Simulium) rufibasis subgroup (Diptera: Simuliidae) in Taiwan - Low, Van Lun; Takaoka, Hiroyuki; Adler, Peter H.; Tan, Tiong Kai; Weng, Francis Cheng-Hsuan; Chen, Cheng-Yu; Lim, Yvonne Ai Lian; Ya'cob, Zubaidah; Chen, Chee Dhang; Sofian-Azirun, Mohd; Wang, Daryi (Springer Verlag (Germany), 2018)
The Simulium rufibasis subgroup is one of three subgroups of the Simulium (Simulium) tuberosum species-group; it is characterized by a pair of clustered stout hairs on the ventral surface of female abdominal segment 7. A member of the S. rufibasis subgroup in Taiwan was investigated morphologically and genetically using the universal cytochrome c oxidase subunit I (COI) barcoding gene and polytene chromosomal banding pattern. The Taiwanese material is morphologically similar to S. rosliramlii Takaoka & Chen from Vietnam and represents the second species of the S. rufibasis subgroup known from Taiwan. It also represents a novel molecular lineage that is distinct from three other primary lineages identified as S. doipuiense, S. doipuiense/S. rufibasis, and S. weji previously reported from Thailand. The mitochondrial evidence for a distinct lineage in Taiwan is supported by chromosomal analysis, which revealed unique sex chromosomes. For nomenclatural stability, we associate the name S. arisanum Shiraki with the Taiwanese entity. Originally described from females from Taiwan, S. arisanum until now has remained an enigmatic species.